Cortical Hyper-Connectivity in a Stroke Patient with Rotated Drawing - Valentina Sebastiani (Karger Publishers, 2021)
In the present case report, we investigated the cortical networks of a patient (DDA) affected by right parietal stroke who showed a constructional phenomenon, in which when coping and recalling from memory a complex figure, the model was reproduced rotated of 90° along the vertical axis. Previous studies suggested that rotation on copy is associated with visuospatial impairments and abnormalities in parietal cortex, whereas rotation on recall might be related to executive deficits and dysfunction of frontal regions. Here, we computed the DDA’s resting-state functional connectivity (FC) derived from cortical regions of the dorsal attention (DAN) and the frontal portion of the executive-control network (fECN), which are involved in the control of visuospatial attention and multiple executive functions, respectively. We observed that, as compared to a control group of right stroke patients without drawing rotation, DDA exhibited selective increased FC of the DAN and fECN, but not of task-irrelevant language network, within the undamaged hemisphere. These patterns might reflect a pathological communication in such networks leading to impaired attentional and executive operations required to reproduce the model in the correct orientation. Notably, such enhancement of FC was not detected in a patient with a comparable neuropsychological profile as DDA, yet without rotated drawing, suggesting that network-specific modulations in DDA might be ascribed to the constructional phenomenon of rotated drawing.